2011
DOI: 10.1074/jbc.m110.182592
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cloning and Catalytic Mechanism of a Novel Glycosphingolipid-degrading β-N-Acetylgalactosaminidase from Paenibacillus sp. TS12

Abstract: We report here the molecular cloning, characterization, and catalytic mechanism of a novel glycosphingolipid-degrading ␤-N-acetylgalactosaminidase (␤-NGA) from Paenibacillus sp. TS12 (NgaP). Consisting of 1034 putative amino acid residues, NgaP shares no sequence similarity with known proteins. Recombinant NgaP, expressed in Escherichia coli, cleaved the nonreducing terminal ␤-GalNAc residues of gangliotriaosylceramide and globotetraosylceramide. The enzyme hydrolyzed para-nitrophenyl-␤-N-acetylgalactosaminide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
25
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 32 publications
2
25
0
Order By: Relevance
“…In subsequent assays we used 2 mmol/L (Z)-Pugnac to ensure complete hexosaminidase A inhibition. To generate the aglycone from the desulfated glycoside, we explored the bacterial enzyme β - N -acetylgalactosaminidase ( β -NGA) (15). The data in online Supplemental Tables 6 and 7 show that β -NGA did not generate aglycones from the sulfated substrates, and β -NGA catalyzed hydrolysis of the non-sulfated GALNS and ARSB products were not sensitive to (Z)-Pugnac.…”
Section: Resultsmentioning
confidence: 99%
“…In subsequent assays we used 2 mmol/L (Z)-Pugnac to ensure complete hexosaminidase A inhibition. To generate the aglycone from the desulfated glycoside, we explored the bacterial enzyme β - N -acetylgalactosaminidase ( β -NGA) (15). The data in online Supplemental Tables 6 and 7 show that β -NGA did not generate aglycones from the sulfated substrates, and β -NGA catalyzed hydrolysis of the non-sulfated GALNS and ARSB products were not sensitive to (Z)-Pugnac.…”
Section: Resultsmentioning
confidence: 99%
“…In our MS/MS study we found that hexosaminidase A present in DBS hydrolyzes the glycosidic linkage of GalNAc-6-sulfate conjugates, therefore it is necessary to include (Z)-Pugnac as an inhibitor of this enzyme so that 4MU release does not occur independently of GALNS. To release 4MU from the GALNS product we used the bacterial enzyme β-N-acetylgalactosaminidase (β-NGA) [5] since we showed in our mass spectrometry study that this enzyme does not act on the GALNS substrate 4MU-GalNAc-6-S and is not inhibited by (Z)-Pugnac [4]. …”
Section: Resultsmentioning
confidence: 99%
“…Previous studies of GH123 members, initially NagP from Paenibacillus sp., 6 and CpNga123 from C. perfringens (whose structure was recently solved) 7 have led to the proposal of a two-step neighbouring group participation mechanism for catalysis ( Figure 1). According to such a mechanism, the enzyme possesses two key active site residues acting in the role of acid/base and transition state stabilization.…”
mentioning
confidence: 99%